Bullous Lupus Erythematosus: A Rare Variant of Acute Cutaneous Lupus Erythematosus - Hazlianda, Cut Putri; Theresia, Calvina (Journal of Pakistan Association of Dermatologists, 2023)
Abstract Acute cutaneous lupus erythematosus (ACLE) is a variant of acute autoimmune disease with distinctive cutaneous manifestations. In addition to its typical manifestations, it can also manifest as bullous lesion, which can be difficult to distinguish clinically from other dermatological disorders. We reported a 40-year-old lady who presented with painful vesicobullous eruptions on malar region since 1 week ago. Patient refused to be examined further and not compliance to the treatment given. She then consumed traditional medicine and admitted to the hospital 2 weeks later with extensive vesicobullous lesions in the face, scalp, trunk and extremities. Patient showed complete remission and excellent clinical response after corticosteroid treatment. This report showed the importance of early diagnosis as well as prompt treatment can result in a better prognosis.